KERUSUHAN SAMPANG: KONTESTASI ALIRAN KEAGAMAAN DALAM WAJAH KEBUDAYAAN MADURA - M. Alie Humaedi (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2014)
The riot in Sampang Madura, on August 26, 2012 is the greatest incident of violence against Shia followers in Indonesia. This conflict has resulted a number of victims, as well as had great material and immaterial losses. The settlement of the conflict has still not been reached. The Sampang riot was caused by many factors—not only the issue of religion, but also the spiritualsocial legitimacy that has economic and political impacts for Sampang’s Shiites. How did the contestation of religious thought lead to a riot – a form of conflict often attributed to Madurese culture? This study uses qualitative methods, specifically in-depth interviews, observations, and use of primary documents. Both actors in the inner and outer ring of perpetrators, victims, motives were investigated. This study finds that the Sampang riot was caused by many factors, including religious debates and the political interests of the religious elite. Specifically, religious elites faced threats to the economic and social legitimacy, thus leading them to frame their actions in the language of cultural practices.